Co-gasification of sewage sludge and lignite coal in supercritical water for H2 production: a thermodynamic modelling approach. (October 2018) - Hantoko, Dwi; Kanchanatip, Ekkachai; Yan, Mi; Lin, Jie; Weng, Zhouchao
Abstract: A non-stoichiometry thermodynamic approach based on Gibbs free energy minimization is developed to predict the performance of hydrogen production from gasification of sewage sludge in supercritical water (SCWG). The study focuses on predicting of the influence of operating conditions on SCWG performance. It was done by varying the reaction temperature (400°C, 500°C, 600°C, 700°C, 800°C), feedstock concentration (5%–50%), and reaction pressure (25 MPa, 30 MPa, and 35 MPa). The potential addition of lignite coal into the process also has been investigated. The prediction results showed that the reaction temperature and feedstock concentration had a stronger influence than the reaction pressure. The higher temperature and lower feedstock concentration favored the hydrogen yield and cold gas efficiency. The addition of lignite coal during gasification of sewage sludge in supercritical water slightly influence to the H2 yield and cold gas efficiency. It was expected that the present work is very helpful for evaluating and optimizing the performance of gasification process in supercritical water.